2000
DOI: 10.1023/a:1008318932641
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related fatigue: Inevitable, unimportant and untreatable? Results of a multi-centre patient survey

Abstract: Fatigue has been identified as an important problem by patients with cancer. It affects more patients for more of the time than any other symptom and is regarded by patients as being more important than either pain or nausea/vomiting. Research into the aetiology and management of this symptom should be regarded as a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
164
3
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(182 citation statements)
references
References 11 publications
3
164
3
12
Order By: Relevance
“…Conclusions about ethnic differences in fatigue severity cannot be drawn because prior studies reported either no differences, 9,10,3941 or higher levels of fatigue in Black patients. 42 Of note in previous studies of patients receiving CTX where no differences in fatigue severity were found, 9,10,3941 90% of the patients were White. The underrepresentation of ethnic minorities in these studies may have limited the power to detect differences in fatigue severity in these patient populations.…”
Section: Discussionmentioning
confidence: 88%
“…Conclusions about ethnic differences in fatigue severity cannot be drawn because prior studies reported either no differences, 9,10,3941 or higher levels of fatigue in Black patients. 42 Of note in previous studies of patients receiving CTX where no differences in fatigue severity were found, 9,10,3941 90% of the patients were White. The underrepresentation of ethnic minorities in these studies may have limited the power to detect differences in fatigue severity in these patient populations.…”
Section: Discussionmentioning
confidence: 88%
“…In prior studies of patients receiving CTX, there are inconsistent associations between ethnicity and mean daily fatigue scores. 7,8,15,36-38 In addition, definitive conclusions about the asssociation of ethnicity and morning and evening fatigue cannot be drawn given the paucity of studies that evaluated diurnal variations in fatigue severity.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty to ninety-six percent of women with breast cancer experience fatigue following diagnosis and treatment (Jacobsen et al, 1999; Longman, Braden, & Mishel, 1999; Portenoy & Itri, 1999; Shimozuma et al, 1999; Stone et al, 2000). Often the first and last symptom experienced during the course of cancer (Longman et al; Portenoy & Itri; Stone et al; Walsh, Donnelly, & Rybicki), cancer-related fatigue (CRF) is reported more frequently than other side effects and can be more disruptive (Wagner & Cella, 2004).…”
mentioning
confidence: 99%